Visual Reinforcement Audiometry used in practice - case reports - Marie Kaniová; Mgr Veronika Švédíková; Anna Tomasová (Listy klinicke logopedie, 2020)
Visual Reinforcement Audiometry (hereinafter referred to as "VRA") is one of the behavioural methods of hearing examination. The case studies aim to provide information on the importance of the aforementioned test and are focused on patients on whom VRA tests are most often performed. The results of the VRA test are beneficial, both in cases of a discrepancy between the results of objective hearing measurements (evoked potentials test, test for the presence of evoked otoacoustic emissions) and the statements by the child's parents, as well as in determining the hearing threshold curve with a hearing aid.